2007
DOI: 10.1093/hmg/ddm363
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of  -synuclein by Siah-1 promotes  -synuclein aggregation and apoptotic cell death

Abstract: Point mutations and gene multiplication of alpha-synuclein cause autosomal dominant familial Parkinson's disease (PD). Moreover, alpha-synuclein- and ubiquitin-positive inclusion bodies are the pathological hallmarks of PD and several other neurodegenerative diseases, such as dementia with Lewy bodies and multiple system atrophy. Despite the presence of ubiquitinated alpha-synuclein species in Lewy bodies, the regulation of alpha-synuclein ubiquitination and its role in Lewy body formation and neurodegeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 75 publications
2
150
0
2
Order By: Relevance
“…Similarly, it has also been shown that CaM binding to mGluR5 inhibits the binding of the E3 ligase Siah-1A in vitro (13). Recently Siah-1A has been shown to promote monoubiquitination of ␣-synuclein, leading to its aggregation (35). It is possible that the effects of CaM on mGluR5 trafficking observed in our study are a consequence of changes in Siah-1A-dependent ubiquitination of mGluR5; however, direct evidence for this hypothesis awaits further experimentation.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, it has also been shown that CaM binding to mGluR5 inhibits the binding of the E3 ligase Siah-1A in vitro (13). Recently Siah-1A has been shown to promote monoubiquitination of ␣-synuclein, leading to its aggregation (35). It is possible that the effects of CaM on mGluR5 trafficking observed in our study are a consequence of changes in Siah-1A-dependent ubiquitination of mGluR5; however, direct evidence for this hypothesis awaits further experimentation.…”
Section: Discussionsupporting
confidence: 62%
“…16,17 Mass spectrometry analysis reveals that SIAH monoubiquitinates α-synuclein at several lysines, including 12, 21 and 23, 16 which were previously found to be monoubiquitinated in purified Lewy bodies. 8 A reason for skepticism regarding a possible role of α-synuclein ubiquitination in Lewy body formation comes from the observation that only a small fraction (about 10%) of α-synuclein is ubiquitinated in Lewy bodies.…”
Section: Role Of Ubiquitin In α-Synuclein Aggregationmentioning
confidence: 91%
“…18 On the other hand, Liu et al recently found that the α-synuclein A30P mutant was not efficiently ubiquitinated by SIAH. 17 The reason for this apparent discrepancy is not clear.…”
Section: Role Of Ubiquitin In α-Synuclein Aggregationmentioning
confidence: 99%
“…Although some ubiquitin-ligases can polyubiquitinate α-synuclein (6-8), the E3 ubiquitin-ligase responsible for α-synuclein monoubiquitination has remained obscure. We and others have recently shown that α-synuclein is monoubiquitinated by the E3 ubiquitin-ligase SIAH both in vitro and in vivo (9)(10)(11). SIAH is present in Lewy bodies (9) and monoubiquitinates α-synuclein at the same lysine residues that are monoubiquitinated in α-synuclein immunopurified from Lewy bodies (5,10).…”
mentioning
confidence: 91%